Health-Related Outcomes and Molecular Methods for the Characterization of A1 and A2 Cow’s Milk: Review and Update - Alina Borş; Silviu-Ionuț Borş; Viorel-Cezar Floriștean (Veterinary Sciences, 2024)
A new trend in cow’s milk has emerged in the market called type A1 and A2 milk. These products have piqued the interest of both consumers and researchers. Recent studies suggest that A2 milk may have potential health benefits beyond that of A1 milk, which is why researchers are investigating this product further. It is interesting to note that the A1 and A2 milk types have area-specific characteristics compared to breed-specific characteristics. Extensive research has focused on milk derivatives obtained from cow’s milk, primarily through in vitro and animal studies. However, few clinical studies have been conducted in humans, and the results have been unsatisfactory. New molecular techniques for identifying A1 and A2 milk may help researchers develop new studies that can clarify certain controversies surrounding A1 milk. It is essential to exercise extreme caution when interpreting the updated literature. It has the potential to spread panic worldwide and have negative economic implications. Therefore, this study aims to investigate the differences between A1 and A2 milk in various research areas and clarify some aspects regarding these two types of milk.